Mortality burden and epidemiology of procedure- and device-related healthcare-associated infections in the United States, 1999–2023: a CDC WONDER analysis - Xie, Lang; Xia, Kaide; Xu, Xiaodong; Zhu, Meisu; Li, Hailing; Wang, Junwen; Chen, Mei (Frontiers in Public Health, 2025)
BackgroundProcedure- and device-related healthcare-associated infections (PD-HAIs) are a major cause of preventable hospital mortality, yet population-level data on long-term trends remain limited. This study aims to evaluate national PD-HAI mortality trends and subgroup disparities in the United States from 1999 to 2023.MethodsThis descriptive study analyzed PD-HAI-related mortality in the United States from 1999 to 2023 using the CDC Wide-ranging Online Data for Epidemiologic Research (WONDER) Multiple Cause of Death database. Deaths involving PD-HAIs were identified using ICD-10 codes. Age-adjusted mortality rates (AAMRs) were calculated per 100,000 population using the 2000 U.S. standard population. Temporal trends were assessed using Joinpoint regression to estimate annual percent changes (APCs) and average annual percent changes (AAPCs) with 95% confidence intervals (CIs). Analyses were stratified by age, sex, race, region, urbanization, and state.ResultsFrom 1999 to 2023, PD-HAI-related mortality declined markedly nationwide, with AAMRs falling from 1.62 to 0.77 per 100,000 and an overall AAPC of −3.02% (p < 0.05). The steepest declines occurred between 2001 and 2014. Reductions were observed across all demographic subgroups, although disparities persisted. Older adult individuals, males, Black populations, residents of the South, and nonmetropolitan areas consistently exhibited higher AAMRs. Black individuals experienced the greatest relative reduction (AAPC = −4.12%), while urban regions showed more pronounced declines than rural areas. State-level analyses revealed substantial heterogeneity in baseline mortality and trends. Although the overall infection-type distribution remained stable, deaths due to infections involving joint prostheses and other implants increased steadily over time.ConclusionDespite national declines in PD-HAI mortality, trends have been less consistent since 2014, and significant geographic and demographic disparities persist. Sustained, state-tailored infection-prevention efforts—prioritizing jurisdictions with little or no progress—are needed as a matter of health equity to further reduce preventable deaths.